2012
DOI: 10.1002/pssb.201084225
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigations on auxetic structures based on recycled rubber

Abstract: The growing demand for tyres in transport industry provides a negative impact on the environment, due to the problems related to recycling and disposal of the rubber waste. However, adding waste tyres as a dispersive phase in polymeric composites has shown high toughness and moderate increase of mechanical strength within the composites. In this work, we investigate the use of recycled rubber core to manufacture auxetic (re‐entrant) honeycomb structures. The re‐entarnt honeycombs produced are evaluated using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Depending on whether negative values of Poisson ratio are observed in all crystallographic directions, in some of them or in none of them, one can define all materials as auxetics, partial auxetics and nonauxetics, respectively (). Recently, increasing interest in studies of auxetic materials and models was observed .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on whether negative values of Poisson ratio are observed in all crystallographic directions, in some of them or in none of them, one can define all materials as auxetics, partial auxetics and nonauxetics, respectively (). Recently, increasing interest in studies of auxetic materials and models was observed .…”
Section: Introductionmentioning
confidence: 99%
“…A further class of materials which is investigated in this issue is that of auxetic composites. Thaís A.A. Silva and co‐workers 12 investigated the use of recycled rubber core composites to manufacture auxetic re‐entrant honeycombs. The authors show that the Poisson's ratio of this honeycomb is dependent on width‐to‐thickness ratio as well as the interaction effect between the ‘width and angle’ and ‘angle and thickness’.…”
mentioning
confidence: 99%
“…The rubber particles were shredded, washed, and dried at 80°C for 24 h and classified by sieving in size range of 100/200 US‐Tyler (0.149/0.079 mm). According to Panzera et al and Silva et al the composite fabricated with 25% of rubber particle size of 100/200 US‐Tyler has shown improved mechanical and physical properties. The addition of 25% of rubber particles into polymeric matrix has shown higher particle packing factor and energy absorption, besides contributing to recycle rubber wastes from scrap tyres.…”
Section: Methodsmentioning
confidence: 99%